Colloquy with Juan José García-Noblejas on understanding communication from the perspective of Aristotle's Poetics - Fuster, Enrique (Church, Communication and Culture, 2022)
In this interview we will explore García-Noblejas’ thought on public communication, which is deeply marked by his interpretation of Aristotle’s Poetics and influenced by some contemporary thinkers. For García-Noblejas, communication is a service and a form of practical knowledge with five dimensions: ethics, politics, rhetoric, aesthetics, and poetics. Poetics is the most important of these, since its symbolic perspective of the representation of human actions allows us to deeply understand the narrative and dramatic texts typical of journalism, advertising, and propaganda, as well as written and audiovisual fiction. Poetics is the art of creating “possible worlds” in which the reader/spectator recognizes himself (or herself) and with which he dialogues starting from his own identity. García-Noblejas defends public communication that is based on the gift of self and looks to community fruitfulness. He also discusses some frequent pathologies in the media. Finally, he proposes his theory of the Second Navigation to discern the meaning of a text and explains why it is necessary to give a transcendent meaning to the Aristotelian concept of catharsis.